Studi Kasus : Dampak Pembangunan PLTU terhadap Kehidupan Sosial, Ekonomi, dan Lingkungan Masyarakat Morowali Utara, Sulawesi Tengah dalam Kaca Mata Sosiologi - Rizqi Ahmad Muzaki; Septian Bintang Cahyo; Tegar Vicho Virdyanto (Lembaga Pengembangan Kinerja Dosen, 2024)
This research explores the impact of the development of Captive PLTU infrastructure in Sulawesi on the lives of local communities from a sociological perspective. Using a qualitative approach and case study design, this research explores the social, economic and environmental changes that occurred as a result of development interventions by PT GNI and PT COR. The construction of the Captive PLTU is based on Presidential Regulation No. 112/2022 concerning the Acceleration of Renewable Energy Development for the Supply of Electric Power. Local residents experience a range of negative impacts, including air pollution, pollution and disruption to livelihoods that depend on natural resources. The damming of the Lampi River by the PLTU has also raised concerns about the potential for flooding and decreased air quality. This research found that this development project has taken away the rights of local communities and caused various human rights violations. The results of this research emphasize the need to revise regulations that are more inclusive and fair to ensure sustainable development that takes into account the balance between economic, social and environmental interests. In conclusion, infrastructure development must be carried out with the active involvement of local communities and careful consideration of its impacts.